2000
DOI: 10.1001/archpsyc.57.11.1061
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Reelin and Glutamic Acid Decarboxylase67 (GAD67) Expression in Schizophrenia and Bipolar Disorder

Abstract: The selective down-regulation of RELN and GAD(67) in prefrontal cortex of patients with schizophrenia and bipolar disorder who have psychosis is consistent with the hypothesis that these parameters are vulnerability factors in psychosis; this plus the loss of the correlation between these 2 parameters that exists in nonpsychotic subjects support the hypothesis that these changes may be liability factors underlying psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
807
5
13

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,136 publications
(896 citation statements)
references
References 34 publications
71
807
5
13
Order By: Relevance
“…Interestingly, these extended TUJ1‐positive structures showed distinct GAD67‐positive protrusions, dendritic spines of inhibitory GABAergic nature suggesting that our in vitro differentiating conditions are physiological (Guidotti et al , 2000). …”
Section: Resultsmentioning
confidence: 89%
“…Interestingly, these extended TUJ1‐positive structures showed distinct GAD67‐positive protrusions, dendritic spines of inhibitory GABAergic nature suggesting that our in vitro differentiating conditions are physiological (Guidotti et al , 2000). …”
Section: Resultsmentioning
confidence: 89%
“…More recently, a decrease in GAD 67 mRNA, but not GAD 65 , expression has again been noted (Guidotti et al 2000). A variety of studies have suggested that GAD 67 is regulated through transcriptional mechanism.…”
Section: Postmortem Evidence For a Gaba Defect In Schizophreniamentioning
confidence: 96%
“…Since mRNA for the two isoforms of GAD are expressed by 95% of the neurons in rat hippocampus (Stone et al 1999), it seems likely that complex cellular mechanisms may be influencing the nature of the results observed in these postmortem studies. The fact that changes in GAD 67 mRNA have been observed not only in schizophrenics, but also in subjects with bipolar disorder (Guidotti et al 2000;Heckers et al 2001) suggests that these changes may be related to a nonspecific factor associated with both disorders. Interestingly, differential expression of mRNAs associated with the two isoforms of GAD have been reported in relation to both acute and chronic stress (Bowers et al 1998), although in this case that for GAD 67 was increased, rather than decreased as it is in schizophrenia and bipolar disorder.…”
Section: Postmortem Evidence For a Gaba Defect In Schizophreniamentioning
confidence: 99%
“…4 In nonhuman primates, normal working memory function depends on GABA-mediated circuitry in the DLPFC 5,6 and decreased levels of the mRNAs encoding the 67 kDa isoform of glutamic acid decarboxylase (GAD 67 ), an enzyme that synthesizes GABA, and GABA transporter 1 (GAT1), a presynaptic transporter for the reuptake of synaptically released GABA, have been replicated in multiple post-mortem studies of schizophrenia. [7][8][9][10][11][12][13] Indeed, an analysis of all post-mortem studies of schizophrenia conducted in specimens from the Stanley Neuropathology Consortium revealed that three genes expressed in GABA neurons (reelin, parvalbumin (PV) and GAD 67 ) had the most abnormal transcript and protein levels in schizophrenia. 14 At the cellular level, the density of neurons with detectable levels of GAD 67 mRNA was significantly decreased in schizophrenia subjects, 7,9 whereas in neurons with detectable levels of GAD 67 mRNA, the expression level per neuron did not differ from control values.…”
Section: Introductionmentioning
confidence: 99%